2014
DOI: 10.1016/j.procir.2014.06.151
|View full text |Cite
|
Sign up to set email alerts
|

Crack Repair of Single Crystal Turbine Blades Using Laser Cladding Technology

Abstract: The formation of cracks in single crystal (SX) turbine blades is a common problem for aero-engines. To repair cracks, which are located under the tip-area, a new method is to clad with single-crystal-technology. This technology use multi-layer cladding to replace the single crystal material. To regenerate cracked material it is necessary to remove the crack affected material. The used notch geometries to remove the crackaffected area must be weldable and also permit the material solidification in the same orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“…Turbine blades are made of heat-resistant steel or nickel/cobalt-based superalloys. Because of the harsh environment and relatively short lifespan of the blades, any opportunity to regenerate damaged element is very attractive [6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Turbine blades are made of heat-resistant steel or nickel/cobalt-based superalloys. Because of the harsh environment and relatively short lifespan of the blades, any opportunity to regenerate damaged element is very attractive [6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…High-pressure single-crystal turbine blades made of Ni-based superalloys have superior creep and fatigue properties with respect to the polycrystalline ones and, accordingly, they can sustain temperatures up to 1100 °C. However, as a consequence of the extreme conditions in the engine of High-pressure single-crystal turbine blades made of Ni-based superalloys have superior creep and fatigue properties with respect to the polycrystalline ones and, accordingly, they can sustain temperatures up to 1100 • C. However, as a consequence of the extreme conditions in the engine of commercial airplanes, they undergo erosion and cracking [90,99,100]. Kaierle et al demonstrated that the DED process had promising results in the building-up of a single crystal or directionally solidified structures, while laser remelting could be used to extend this monocrystalline height [99].…”
Section: Repaired By Thermal Spraymentioning
confidence: 99%
“…Results of metallographic studies showed the existence of clear boundary between the base and built-up material, absence of defects and fine-needled structure of built-up layer indicating high cooling speeds. In respect to the advantages of used methods the authors also mentioned its adaptivity, тельным результатом стало наличие системы контроля геометрии наплавленных валиков с целью обеспечения минимального припу-ска на последующую механическую обработку, а так же оценки технологической возможно-сти "лечения" поверхностных трещин лопаток из никелевых сплавов при лазерной наплавке [21][22][23].…”
Section: Fig 4 Cracks and Porosity In Built-up Layer On The Blade Ounclassified
“…Also, authors mention the advantages of fiber laser in comparison with СО 2 laser. The positive result consisted in the presence of control system of weld bead geometry for the purpose of provision of minimum allowance for the further mechanical treatment; also the evaluations of technological capacity of "treatment" of surface cracks of the blades of nickel alloys during the laser cladding were mentioned in the papers [21][22][23].…”
Section: рис6 макет адаптивного автоматизированного ком-плекса лазеmentioning
confidence: 99%